206k views
3 votes
I tried to do this problem but not sure why I got this question incorrect.

I tried to do this problem but not sure why I got this question incorrect.-example-1
User Uraza
by
5.1k points

1 Answer

7 votes

Answer is :


\begin{gathered} \begin{bmatrix}{2} & {8} \\ {6} & {3}\end{bmatrix}\begin{bmatrix}{3} & {0} \\ {2} & {-1}\end{bmatrix}\text{ } \\ a1\text{ = (2}\cdot3)\text{ + (8}\cdot2)\text{ = 6+16 = 22} \\ a2\text{ = (2}\cdot0)+(8\cdot-1)\text{ = 0 -8 = -8} \\ b1=(6\cdot3)\text{ + (3}\cdot2)\text{ = 18 + 6 = 24 } \\ b2\text{ = (6}\cdot0)+(3\cdot-1)\text{ = 0 -3 = -3 } \\ \text{Therefore the final matrix will be :} \\ \begin{bmatrix}{22} & {-8} \\ {24} & {-3}\end{bmatrix} \end{gathered}

User Green Cloak Guy
by
4.7k points